PARTISIPASI ULAMA DI SULAWESI SELATAN DI DALAM AKTIVITAS POLITIK DAN KEMASYARAKATAN - Haidir Fitra Siagian; Mohd. Yusof Haji Abdullah; Normah Mustaffa (Fakultas Dakwah dan Komunikasi, 2015)
This paper discusses the participation of the clergy in political and social activities in South Sulawesi, Indonesia. Ulama is an Islamic leader who has extensive knowledge of religious affiliation. Scholars can affect the community, as it is believed by the people, he has charisma, and he respected her advice is also an example to the community. As the unofficial leader, cleric is to be responsible for all aspects of development, including in the political and social activity. Participation of scholars in the development is very important, as direct beneficiaries of development and an active contributor to the development process. The results of this study indicate that there are scholars in the South who are actively involved in political and social activities. In political activity, there are scholars who are members of political parties and there are scholars who participated in the campaign for a candidate running in the election. Similarly in social activities, there are scholars involved in volunteer work such as building mosques, protecting their lives, attend community meetings, participate in community sports activities, attend celebrations taking place in society, as well as providing assistance to disaster.